KNOWLEDGE, PRACTICE AND RELATED FACTORS REGARDING SAFE INJECTION AMONG NURSES AT BACH MAI HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: To assess the current status of knowledge and practice among reagarding safe injection nurses at Bach Mai Hospital and to identify associated factors.Methods: A cross-sectional descriptive study was conducted among 481 nurses in clinical departments from August to November 2024. Participants were selected by stratified random sampling. Knowledge was collected using a 35-item questionnaire consisting of four domains; practice was assessed through direct observation using a 30criterion checklist. Data were analyzed using SPSS 20 software with descriptive statistics and Chisquare test to explore related factors.Results: Overall, 81.9% of nurses achieved general safe injection knowledge; the highest knowledge score was for general principles of safe injection (92.5%), and the lowest was for infection control (71.7%). The proportion of nurses performing safe injections was 61.1%; nurse preparation, patient preparation, and equipment preparation were above 92%, whereas techniques for drug withdrawal and injection were lower (69%). Gender and participation in safe injection training were statistically associated with knowledge (p  0.05).Conclusion: Nurses at Bach Mai Hospital were at a good level of safe injection knowledge and practice. However, knowledge and practice related to infection control and injection technique were limited, requiring enhanced training and regular supervision. These findings provide important evidence to develop training programs and quality improvement.
Keywords: Knowledge, practice, safe injection, nursing.